Etiological spectrum of pneumonia in children in Kyiv, Ukraine - V.E. Khomenko; O.V. Iemets; O.P. Volosovets; S.P. Kryvopustov; O.V. Mozyrska (Zaslavsky O.Yu., 2023)
Background. In Ukraine over the past 20 years, the incidence of pneumonia in children has increased. The aim of the study is to assess the contribution of respiratory viruses and bacteria to pneumonia in children in Ukraine. Materials and methods. The etiology of community-acquired pneumonia was studied in 175 children at Medical Center "Eurolab" and Clinical Hospital 2 (Kyiv, Ukraine) over 2018-2022. Viral and bacterial pathogens were detected using polymerase chain reaction, chromatographic immunoassay. Results. The prevalence of viral pneumonia among total cases of pneumonia was 78.9 % in Kyiv during 2018-2022. Thirty-seven (21.1 %) cases of CAP were classified as bacterial. The most common were respiratory syncytial virus (18.1 %), metapneumovirus (13 %), adenovirus (10.1 %), parainfluenza virus (10.1 %). The other causative viral agents were influenza virus type A (7.2 %), rhinovirus (5 %), bocavirus (2.9 %), SARS-CoV-2 (1.4 %) and measles virus (1.4 %). Etiological spectrum is similar to the results of studies conducted in other European countries. Conclusions. Respiratory viruses, particularly respiratory syncytial virus and metapneumovirus, are the major contributors to community-acquired pneumonia in children in Kyiv.